Cities of Refuge: An Exploration of Sanctuary and Restorative Culture in the Hebrew Bible - Reaves, Jayme R. (Studies in Christian ethics, 2023)
The cities of refuge as detailed in the Deuteronomic witness in the Hebrew Bible have served as the inspiration and model for the practice of providing sanctuary for many throughout the centuries, namely with the most recent Sanctuary movements in the US and the UK in the twentieth and twenty-first centuries. And yet, its biblical witness as to its implementation and effectiveness is practically silent. Using methods of biblical studies via liberation hermeneutics and theological ethics from both the Jewish and Christian traditions, the following questions will be explored: What were the cities of refuge? How were they to be set up? What are the theological and ethical questions at play in the biblical witness as to their use? What relevance, if any, do they have for us today?